AhABI4s Negatively Regulate Salt-Stress Response in Peanut - Luo, Lu; Wan, Qian; Zhang, Kun; Zhang, Xiurong; Guo, Ruijie; Wang, Cai; Zheng, Chengchao; Liu, Fengzhen; Ding, Zhaojun; Wan, Yongshan (Frontiers in Plant Science, 2021)
Soil salinity is one of the major factors that limits the area of cultivable land and yield potential of crops. The ability of salt tolerance varies with plant species. Peanut is a moderately salt sensitive, economically-important crop, however, its biological processes involved in salt stress response remain unclear. In this study, we investigated the role of AhABI4 in salt tolerance and elucidated its mode of action in peanut. The results showed that down-regulation of AhABI4s via whole plant virus-induced gene silencing enhanced survival rate, biomass accumulation and root/shoot ratio of peanut seedling in response to salt stress. Transcriptomics, quantitative proteomics and phosphoproteomic analyses were preformed using AhABI4s-silenced and Mock plants. Expression pattern of 15,247 genes, 1,900 proteins and 2,620 phosphorylation sites were affected by silencing of AhABI4s in peanut leaf and root after NaCl treatment. Among them, 63 potential downstream target genes of ABI4 changed consistently at both transcription and translation levels, and the protein/phosphorylation levels of 31 ion transporters/channels were also affected. Electrophoretic mobility shift assays (EMSA) showed that ABI4 was able to bind to the promoters of HSP70, fructokinase (FRK) and pyruvate kinase (PK) coding genes in vitro. In addition, we also detected a binding preference of AhABI4 for CACT(G/T)GCA motif in the promoters of down-regulated genes in peanut leaf. Collectively, the potential down-stream targets, regulated at the levels of transcription and translation, binding preference, and in vivo phosphorylation sites revealed in this study will provide new insight into AhABI4-mediated salt tolerance regulation mechanism in peanut.